2021
DOI: 10.1302/2633-1462.210.bjo-2021-0069.r1
|View full text |Cite
|
Sign up to set email alerts
|

Lower pelvic tilt, lower pelvic incidence, and increased external rotation of the iliac wing in patients with femoroacetabular impingement due to acetabular retroversion compared to hip dysplasia

Abstract: Aims The effect of pelvic tilt (PT) and sagittal balance in hips with pincer-type femoroacetabular impingement (FAI) with acetabular retroversion (AR) is controversial. It is unclear if patients with AR have a rotational abnormality of the iliac wing. Therefore, we asked: are parameters for sagittal balance, and is rotation of the iliac wing, different in patients with AR compared to a control group?; and is there a correlation between iliac rotation and acetabular version? Methods A retrospective, review boar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 64 publications
(125 reference statements)
2
18
0
7
Order By: Relevance
“…However, the ischial spine sign suggests that these appearances are partially a feature of external rotation of the hemipelvis, 9,10 and more recent work suggests that in addition to this external rotation deformity, there is some degree of prominence of the iliac wing anteriorly, 11 as well as lower pelvic tilt (PT) angle and external rotation of the iliac wing. 12 Functional acetabular retroversion has been associated with PT, 13 and the effect of PT on the interpretation of radiological parameters, in particular the assessment of acetabular retroversion, has been clearly illustrated. 14,15 Positional changes in PT have previously been reported in patients with developmental dysplasia of the hip (DDH), [16][17][18][19][20] undiagnosed hip pain, 21,22 and awaiting total hip arthroplasty (THA), 23 but have not yet been studied in patients with acetabular retroversion.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ischial spine sign suggests that these appearances are partially a feature of external rotation of the hemipelvis, 9,10 and more recent work suggests that in addition to this external rotation deformity, there is some degree of prominence of the iliac wing anteriorly, 11 as well as lower pelvic tilt (PT) angle and external rotation of the iliac wing. 12 Functional acetabular retroversion has been associated with PT, 13 and the effect of PT on the interpretation of radiological parameters, in particular the assessment of acetabular retroversion, has been clearly illustrated. 14,15 Positional changes in PT have previously been reported in patients with developmental dysplasia of the hip (DDH), [16][17][18][19][20] undiagnosed hip pain, 21,22 and awaiting total hip arthroplasty (THA), 23 but have not yet been studied in patients with acetabular retroversion.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we did not standardize the values for AV to the anterior pelvic plane and had no three-dimensional information [ 52 ]. Given a mean pelvic tilt of 4° in a supine position, we could generally have underestimated AV [ 53 ]. However, by using the same method of previous studies [ 45 ], this allows for a direct comparison to the reported values from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…But we excluded patients with degenerative changes for the control group, therefore we believe that there should be no relevant bias. Another limitation is, that we did not evaluate the influence of pelvic tilt [51] on AV measurement. Previous studies using 3D models evaluated standardized measurements of AV while normalizing pelvic tilt [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of the cross over sign (intersection of blue and red line) and of the retroversion index (X divided by Y) on schematic view is shown (B). Figures reprinted with permission from [51] …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation